Prevalence and Outcome of Neonates presenting with Hypoxic Ischemic Encephalopathy - Shafa; Aisha Tuz Zohrah; Riaz, Wajeeha; Eemaan, Farrah; Shaikh, Salma (Indus Journal of Bioscience Research, 2025)
Objective: To determine the prevalence and outcome of neonates presenting with hypoxic ischemic encephalopathy. Study Design: Observational descriptive study Setting: Department of Pediatrics, Neonatal care unit, Bilawal Medical College for Boys, LUMHS, Jamshoro. Duration: April 15, 2025 to July 15, 2025. Methodology: A total of 65 term newborns (delivered at ≥37completed weeks of gestation) with Hypoxic Ischemic Encephalopathy of either gender, birth weight > 2000 g were included. Newborn with Hypoxic ischemic encephalopathy was labelled as positive if she/he had low APGAR scores (< 7 at 5 min), intrapartum asphyxia (PH < 7.0, or base deficit ≥ 12.0 mmol/l) and had at least 2 of the following clinical features like state of abnormal consciousness, impaired sucking, swallowing or feeding difficulty and Hypotonia. Further HIE was graded using the Modified Sarnat Encephalopathy Grading (MSEG) system. All the newborns with HIE were managed according to standard operating systems at the unit and were followed up by a daily clinical examination and outcomes of HIE i.e., mortality and discharge were assessed on 7th day. Results: A total of 65 newborns with asphyxia were included in this study. Mean age of the mothers was 28 ±2.5 years. Mean infant age was 2.73±1.31 days and mean gestational age was 38.68±1.24 weeks. 33 (50.7%) were male and 32 (49.2%) were female. 34 (52.3%) delivered vaginally and 31 (47.69%) through C-section. 7 (10.7%) newborn Neonates had Hypoxic Ischemic Encephalopathy. 3 (42.8%) of the babies suffered from hypoxic ischemic encephalopathy grade I & grade-II each, grade III was found to be 1 (14.2%). Mortality occurred in 2 cases (28.5%) of HIE, 1 was from grade-I and 1 was from grade-III. Conclusion: This study reveals high prevalence of Hypoxic Ischemic Encephalopathy in birth asphyxia newborns. The severity of HIE affects the outcome of newborns having birth asphyxia, with HIE grade III associated with maximum mortality.%.